فقه المحدثين من خلال تراجم الأبواب، حديث "خذي ما يكفيك وولدك بالمعروف"دراسة تحليلية مقارنة: Muhaddithīn’s Jurisprudence Through Tarājim Abwāb: A Case Study of the Ḥadīth: "Take What Reasonably Suffices You and Your Child": An Analytical Comparative Study - أحمد عبد الله عيد المخيال (الدراسات الإسلامية, 2024)
This research highlights the jurisprudential orientation of Ḥadīth scholars as reflected in their scholarly works, thereby addressing the assertion that they lack jurisprudential insight in their narrations. By investigating the biographical entries of Ḥadīth compilations, the study meticulously extracts Ḥadīth from their primary sources and analyses their associated biographical contexts. A particular focus is placed on the Prophet Muhammad’s (peace be upon him) guidance to Hind bint Utbah in response to her inquiry, alongside the jurisprudential rulings derived from this incident. The study aims to demonstrate the jurisprudential tendencies of Muhaddithin through their interpretations and applications of this Ḥadīth, emphasising how their legal reasoning is embedded within their narrations. By elucidating the Prophet’s (peace be upon him) position in this guidance, the research underscores the jurisprudential depth of Ḥadīth scholars, particularly during the third Hijri century, when their legal insights became prominently evident in their biographical works. The findings reveal that Ḥadīth scholars not only narrated Ḥadīth but also engaged in rigorous jurisprudential analysis, as exemplified by the perspectives of eight prominent scholars who discussed this Ḥadīth in their compiled books of Ḥadīth. These scholars unanimously affirmed that the Prophet’s (peace be upon him) guidance serves as a foundational source for issuing fatwas and establishing Sunnah, deviating from it is only possible when supported by compelling evidence The research concludes that the Prophet (peace be upon him), as the messenger of Allah Almighty, provided clear and comprehensive guidance, which Ḥadīth scholars meticulously preserved and interpreted within the framework of Islamic jurisprudence. This study thus reaffirms the integral role of Ḥadīth scholars in shaping Islamic legal thoughts and their profound contributions to the understanding and application of the Sunnah.